Erich Fromm and Left Strategy
XI, 320 p. 1 illus.
Keywords: This book reconsiders the significance of the work of Erich Fromm and its relevance for contemporary radical Left strategy. Through this reassessment the volume seeks to contribute to the revitalization of critical social theory and its relationship to radical praxis. A key theme running throughout the volume is that Fromm’s humanist socialism offers a unique set of critical tools for re-assessing entrenched assumptions and debates within the contemporary radical Left about what struggles against capitalism and myriad forms of interrelated social oppressions look like and how they are engaged. Four vantage points are explored in the collection. The first focuses on the question of what Fromm’s theoretical contributions can tell us about what radical activism and resistance ought to look like across multiple terrains of struggle. The second asks what Fromm’s insights regarding social character can tell us today about the forces that stifle productiveness and reproduce domination. In a more utopian vein, it asks what society might look like once domination has been eliminated. The third places Fromm in dialogue with diverse voices on the Left, including prominent psychoanalysts and social and political theorists, in attempts to address lingering tensions and disagreements about radical social change. The fourth asks why the far Right has gained ground politically in recent years and what can be done to counter it from the Left, offering psychoanalytically inflected reflections on the pernicious effects of group narcissism on political agency. Joseph Fantauzzi is a PhD candidate in the Department of Politics at York University, Toronto. Maor Levitin holds a PhD in Politics from York University, Toronto. Terry Maley is Associate Professor of Politics at York University, Toronto, Canada. He is co-editor ofCritical Theory in Dark Times: Marcuse’s Thought in the Neoliberal Era (Palgrave, 2023) and Envisioning Democracy: New Essays After Sheldon Wolin’s Political Thought (2023) .